Chromophobe renal cell carcinoma with sarcomatoid differentiation containing various heterologous components. Issue 9 (17th July 2018) - Hyodo, Toshiki; Kanzawa, Maki; Hara, Shigeo; Takahashi, Kosuke; Ogawa, Satoshi; Furukawa, Junya; Fujisawa, Masato; Kobayashi, Anna; Kuroda, Naoto; Itoh, Tomoo
Abstract : Renal cell carcinoma (RCC) occasionally has sarcomatoid differentiation and rarely contains heterologous components. We report a case of chromophobe RCC with sarcomatoid differentiation that had various heterologous components including a unique lipomatous area. The patient was an 83‐year‐old woman with a palpable mass in the left lower abdomen. Grossly, the tumor was 14 cm in diameter and had yellowish‐to‐whitish color with focal necrosis and hemorrhage. Histologically, the tumor was composed of an eosinophilic subtype of chromophobe RCC with sarcomatoid differentiation including mainly chondrosarcoma, some osteosarcoma and a lipomatous area. The heterologous components of sarcomatoid RCC are usually osteosarcoma or chondrosarcoma, and sarcomatoid RCC with multiple heterologous components is extremely rare.